Association between lipid variability and the risk of mortality in cancer patients not receiving lipid-lowering agents - Kim, Seohyun; Kim, Gyuri; Cho, So Hyun; Oh, Rosa; Kim, Ji Yoon; Lee, You-Bin; Jin, Sang-Man; Hur, Kyu Yeon; Kim, Jae Hyeon (Frontiers in Oncology, 2023)
Aim We investigated the association between total cholesterol (TC), low-density lipoprotein (LDL) cholesterol, high-density lipoprotein (HDL) cholesterol, and triglyceride (TG) variability and cancer patient mortality risk. Methods We retrospectively analyzed 42,539 cancer patients who were not receiving lipid-lowering agents and who had at least three TC measurements within 2 years of their initial cancer diagnosis. Using a multivariable Cox regression model, the risk of mortality was evaluated. Results In multivariable analysis, Q2 (adjusted hazard ratio [aHR]: 1.32, 95% confidence interval (CI): 1.24–1.41), Q3 (aHR: 1.66, 95% CI: 1.56–1.76), and Q4 (aHR: 1.96, 95% CI: 1.84–2.08) of coefficient of variation (CV) in TC were significantly associated with mortality risk compared to Q1, showing a linear association between higher TC variability and mortality (P for trend<0.001). Q2 (aHR: 1.34, 95% CI: 1.06–1.77), Q3 (aHR: 1.40, 95% CI: 1.06–1.85), and Q4 (aHR: 1.50, 95% CI: 1.14–1.97) were all significantly associated with a higher risk of death compared to Q1 in multivariable Cox regression for the association between CV in LDL and all-cause mortality (P for trend=0.005). Conclusion In cancer patients who do not receive lipid-lowering agents, high variability in total cholesterol and LDL cholesterol levels was found to pose significant role in mortality risk.